Toleransi Antar Umat Beragama Dalam Perspektif Al-Quran - Ali Akbar; Edi Hermanto; Guslina Siregar; Naila Agnia Ramadhani; Saima Putri Nurfatimah Nst (Indo Publishing, 2025)
In today’s world, characterized by an ever-growing mix of different cultural, religious, and ideological perspectives, it is unavoidable for individuals to engage with one another. This rich diversity serves as a positive force that enhances community bonds and fortifies social cohesion. Nevertheless, religious variances often lead to misunderstandings, strains, and, at times, disputes that threaten fundamental human values. Consequently, it is crucial to reflect on the principles of tolerance highlighted in Islamic teachings, especially those found in the Qur’an. As the sacred text for Muslims, the Qur’an embodies key tenets of tolerance, illustrated in Surah Al-Kafirun verse 6: “To you your religion, and to me mine,